Idiosyncratic aspects of braille transcription for keyboards based on the play "Gaúcho, O Corta-Jaca de cá e lá" by Chiquinha Gonzaga - Rocha Franco, Jéssica de Almeida; Franco Rocha, Jonathan de Aquino (Comparative Cultural Studies: European and Latin American Perspectives, 2023)
This article reflects about the conditions of production and distribution of music scores in braille code for blind and low vision musicians in Brazil, based on objective data from the census carried out by the Brazilian Institute of Geography and Statistics in 2010 about visually impaired people in Brazil. Reflects as well in the Brazilian Law of Inclusion of Persons with Disabilities, of 2015, about accessible materials for that audience. Such data give the reality of braille transcription the need to encourage the training of editors and the distribution of scores. The choice of a composition by Chiquinha Gonzaga for braille transcription was due to the fact that the composer was not only a prominent musician of her time, but also played a leading role in women and stood out for her pioneering spirit in areas previously dominated by the men, opening the way for subsequent generations to continue in the musical environment with more egalitarian ideals. As the composer, the braille music still fights for an equal place in the music scene. Through an overview of the problems of braille transcription of keyboard scores, this article presents particularities of this way of writing and reading music and reasons why such a service requires a solid professionalization.